Gestión del presupuesto en la microempresa novedades el Éxito 2 de la Ciudad de Babahoyo. - Santistevan Avilés, Rosa María (2022)
The present case study is based on the fact that in the El Éxito 2 novelties microenterprise there is no accountant who prepares the budget of the entity, they do not have a person trained to properly handle budget issues, in this way the organization is affected. by not obtaining the desired profits in the economic sphere of the microenterprise. Due to this reason, it has been proposed as an objective to analyze the economic budget of the microenterprise and in this way a clear understanding of how the general administration of the entity is formed is obtained, since this is the main support for the microenterprise to have a long-term sustainable growth. In order to achieve effective administration, it is important to have suitable and trained people to fulfill this role in the microenterprise and thus improve its financial management.